IMPACT OF CALCIUM CHLORIDE ON THE CHEESE YIELD DURING SWISS CHEESE MANUFACTURING PROCESS - Sobirova, Mohichehra; Mohamed, Rifky; Farmonov, Jasur; Samadiy, Murodjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This study is focus on the impact of calcium chloride on the cheese yield and sensory properties during Swiss cheese manufacturing process. Therefore, a research plan was developed to change the amount of calcium chloride and tested for the yield in grams and sensory analysis using Friedman 5 point scale test. It was revealed that the calcium chloride addition is having a positive correlation and the optimum level of adding calcium chloride in cheese was 0.02% and while having decreasing rate of yield when it was increase beyond 0.02%. also, sensory properties of the cheese revealed that the 0.02% of calcium chloride was having good sensory and organoleptic properties and there was a taste issue observed when the calcium chloride increased beyond 0.02%. Therefore, it can be concluded that the calcium chloride is having a strong linkage between casein protein and it induces the reaction rate while increase the yield of the cheese and the sensory qualities of Swiss cheese manufacturing process.